Pengaruh Firm Characteristics Dan Board Characteristics Terhadap Corporate Social Responsibility Disclosure (Jurnal Paradigma Akuntansi, 2022)
The purpose of this research was to examine the effect of firm size, profitability, proportion of female directors, board size and leverage on CSR disclosure in manufacturing companies listed in the Indonesian Stock Exchange during the year 2017-2019. The research was conducted with a sample of 31 data from manufacturing companies. Furthermore, data collection techniques used in the research was purposive sampling. The data was processed using Eviews 11 program. The t test results showed that firm size had positive effect on CSR disclosure, while profitability, proportion of female directors, board size and leverage had no effect on CSR disclosure. The implication of this study was to increase the reliabilility of company’s financial report and to reduce the information asymmetry occurred between management and stakeholders.